2002
DOI: 10.1021/ol010272m
|View full text |Cite
|
Sign up to set email alerts
|

Regiocontrolled Synthesis of the Trimeric Quinone Framework of Conocurvone

Abstract: [reaction: see text] The trimeric quinone framework of conocurvone is crucial for its potent anti-HIV activity. A new synthesis of trimeric quinones based on stepwise substitution of the halogens in 2,3-dihaloquinones by hydroxyquinone anions is described. Chlorinated biquinones are key intermediates that undergo regiospecific substitution reactions to yield trimeric quinone monomethyl ethers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
37
0
1

Year Published

2002
2002
2017
2017

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 36 publications
(38 citation statements)
references
References 15 publications
0
37
0
1
Order By: Relevance
“…In an effort to synthesize anti-retrovirals, Emadi et al previously reported the regiocontrolled synthesis of symmetrical and asymmetrical dimeric and trimeric naphthoquinones by using a novel method [4], [5]. Several of the dimeric naphthoquinones (binaphthoquinones) inhibited HIV-1 integrase with ID 50 (concentration of drug required to inhibit HIV-1 mediated cytopathogenicity in infected cells by 50%) ranging from 1 to 3.5 micromolar [6].…”
Section: Introductionmentioning
confidence: 99%
“…In an effort to synthesize anti-retrovirals, Emadi et al previously reported the regiocontrolled synthesis of symmetrical and asymmetrical dimeric and trimeric naphthoquinones by using a novel method [4], [5]. Several of the dimeric naphthoquinones (binaphthoquinones) inhibited HIV-1 integrase with ID 50 (concentration of drug required to inhibit HIV-1 mediated cytopathogenicity in infected cells by 50%) ranging from 1 to 3.5 micromolar [6].…”
Section: Introductionmentioning
confidence: 99%
“…A high yielding one step synthesis of dimeric naphthoquinones 1–3 was described by us previously 8 and has been subsequently utilized by other research groups 910 to study the synthesis and biological properties of this unique class of compounds.…”
Section: Resultsmentioning
confidence: 99%
“…3 A special subgroup of these compounds is constituted by 2-hydroxynapthoquinones. 4,5 Natural 2-hydroxynaphthoquinones vary in structural complexity from the simple hydroxynaphthoquinones such as 2-hydroxy-1,4-naphthoquinone (lawsone, 1), the main component of a natural hair dye and a potent detector of latent finger marks on cloth or paper under infrared light, 6 to hydroxyphenylnaphthoquinones 3 or complex structures such as the trimeric hydroxynaphthoquinone conocurvone (2), a potential anti-HIV agent 7,8 (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%
“…Stagliano accomplished the arylation of lawsone and its derivatives through a Stille-type coupling reaction of their phenyliodonium ylides with arylstannates (Scheme 1). 7,8,26 Indolyl derivatives of lawsone have also been obtained from the coppercatalyzed reactions of its phenyliodonium ylide (8) with indoles. 27 Besides, a variety of aryl and heteroaryl derivatives of lawsone as well as the 3-styryl-lawsone have been attained through the Suzuki-type coupling of the same iodonium ylide with the appropriate aryl, heteroaryl and styryl boronates.…”
Section: Introductionmentioning
confidence: 99%